(untitled) (Baghdad Science Journal, 2021)
The present study has been carried out to estimate heavy metals mobility, bioconcentration and transfer from polluted soil to roots tissues and from roots tissues to aerial parts using bioconcentration factor and translocation factor. Soil samples and the biomass of the eight vegetable species have been collected during summer season, 2019 from four different sites in Wadi Al-Arg, Taif Governorate, KSA. In general, heavy metals content of soil samples in site III and IV have recorded elevated values compared with those of site I and II. The soil from site IV has shown the highest concentration of Mn, Ni, Cr, Pb, Cu, and Cd amounted 31.63, 14.05, 13.56, 22.79, 31.02 and 2.98 mg/kg dry soil respectively, while the soil from site III has shown the highest concentration of Zn. The data referred to the fact that Mentha longifolia, Cucumis sativus, Capsicum annuum, Lactuca sativa Cucurbita pepo, and Anethum graveolens that grown in sites of investigation could be recognized as suitable for human consumption. These six vegetables could accumulate the measured heavy metals in their tissues with acceptable quantities, less than the permissible levels of Food and Agriculture Organization of the United Nations (FAO). Otherwise, heavy metal concentrations in Solanum lycopersicum and Solanum melongena have been found to be higher than permissible limits of FAO. Both plants also have shown elevated bioconcentration factors values for most of measured heavy metals. For S. lycopersicum the bioconcentration factor values of Fe, Cd, Cu, Pb, Cr, Mn, Ni, and Zn have been found to be 42.150, 27.250, 1.023, ND, 5.926, 4.649, 29.409, and 0.459 respectively. While for S. melongena, they have been 2.360, 21.333, ND, 0.170, ND, 3.113, 50.318, and 0.623, respectively. To avoid the harmful effects of the heavy metals accumulation on human health, consideration should be given to the constant examination to the edible parts of the vegetables grown in heavy metals contaminated soil.